Sick building syndrome in public buildings and workplaces - Abdul-Wahab, Sabah, A.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
Sick Building Syndrome in Public Buildings and Workplaces is the first book of its kind to examine the issue of the interior environment and sick building syndrome in public buildings and workplaces worldwide. Through a comprehensive review of the personal experiences of people who have suffered the symptoms of sick building syndrome, the stories of professionals who have investigated reported occurrences of sick building syndrome, an extensive review of previously published literature on sick building syndrome and the opinions of international experts from a wide variety of fields the causes of sick building syndrome have been identified in this book. Information from this book can be used to provide a healthy safe indoor environment for employees and everyone who enters your building.  Advice is provided on how to identify the causes of sick building syndrome in public buildings, workplaces and other buildings. The health effects of sick building syndrome, the influence of these symptoms on people's work performance, impact on their life and the economic costs of sick building syndrome are examined.  Assessment tools for identifying incidences of sick building syndrome are provided.  Risk control measures that can be implemented in the design and construction stage of buildings, for ventilation systems, biological causes, physical and chemical causes, ergonomic factors and factors that enhance the effects of sick building syndrome are documented.  This book can be used for teaching, research, professional reference and for personal use to maintain a healthy indoor environment.
Introduction to sick building syndrome -- Research based case studies on sick building syndrome.-Indoor air quality.-Perceived IEQ conditions: Why the actual percentage of dissatisfied persons is higher than standards indicate -- Sick building syndrome from a public health perspective.-Dust and microbial contamination in air-conditioning systems and IAQ assessment for public buildings -- Building biology and examination models for buildings.-The influence of school environment on the development of asthma and allergy -- Biological hazards in library buildings: Microbial ecology of the indoor environment -- Mold in library buildings (biological contamination caused by bacteria, viruses, and molds -- Biological hazards in library buildings: Moulds inside compactus shelving -- Is your library building sick? A case study from the main library of Sultan Qaboos University at Oman -- Environmental sensory design -- Sick building syndrome and confounding -- Poor indoor air quality: Investigation of air pollution in large-scale public buildings and of employees personal exposure level -- Assessment of chemical hazards in sick building syndrome situations: Determination of concentrations and origin of VOCs in indoor air environments by dynamic sampling and TD-GC/MS analysis -- Sick building syndrome-environmental and psychosocial hazards: Experience from Croatia -- Building related illnesses -- Environmental health surveys: Occupant satisfaction survey as a tool to improve IEQ -- Sick building syndrome from an architectural perspective -- Sick building syndrome from a psychological perspective: The role of demographic and psychosocial factors in predicting SBS symptoms in workplaces -- Epidemiologic investigation methods for sick building syndrome in public buildings -- Sick building syndrome from a medical perspective: Noninvasive health assessment methods in sick building syndrome -- Solving indoor environmental problems: What can be found out using individual studies -- Building design, maintenance and sick building syndrome risk control measures.
Electronic reproduction.
Keywords: Sick building syndrome; Electronic books